2019
DOI: 10.3389/fimmu.2019.02910
|View full text |Cite
|
Sign up to set email alerts
|

Gut and Lung Microbiota in Preterm Infants: Immunological Modulation and Implication in Neonatal Outcomes

Abstract: In recent years, an aberrant gastrointestinal colonization has been found to be associated with an higher risk for postnatal sepsis, necrotizing enterocolitis (NEC) and growth impairment in preterm infants. As a consequence, the reasons of intestinal dysbiosis in this population of newborns have increasingly become an object of interest. The presence of a link between the gut and lung microbiome's development (gut-lung axis) is emerging, and more data show as a gut-brain cross talking mediated by an inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 117 publications
(138 reference statements)
2
83
1
1
Order By: Relevance
“…The homogenisation effect observed might be a natural response of the gut microbiome towards the changes from womb to birth in which a smaller subset of available microbial populations was preferentially selected. It is notable that the higher Tenericutes observed in preterms' meconium compared to the terms is consistent with the composition of placental microbiome in preterm neonates (29,30). It is interesting to note that the divergence in preterm and term microbiomes was strongest at month 12.…”
Section: Discussionsupporting
confidence: 59%
“…The homogenisation effect observed might be a natural response of the gut microbiome towards the changes from womb to birth in which a smaller subset of available microbial populations was preferentially selected. It is notable that the higher Tenericutes observed in preterms' meconium compared to the terms is consistent with the composition of placental microbiome in preterm neonates (29,30). It is interesting to note that the divergence in preterm and term microbiomes was strongest at month 12.…”
Section: Discussionsupporting
confidence: 59%
“…Hence, distinct identifiable differences in functionality may predict subsequent infection-mediated outcomes [43]. Intriguingly, there is evidence that the developing organ systems at risk for long-term sequelae have a significant cross talk via the microbiome-immune interaction (gut-brain axis, gutlung axis, gut-heart axis) [44]. This emerging field of research offers new targets for microbiota stabilization in order to strengthen the ability to downregulate or resolve immune responses.…”
Section: Sustained Inflammation In the Context Of Preterm Birthmentioning
confidence: 99%
“…Therefore, the importance of early microbiome development on host health and morbidity and the relative plasticity of this community presents a need and an opportunity to colonize the preterm gut microbiome with beneficial organisms that maximize ecosystem services to the host [23]. These services include increased availability of nutrients from human milk, improved maturation of the intestinal epithelium, reduced enteric inflammation, and mitigated risk of infection in hospitalized infants [3,21,43,44,46]. In this study, we found preterm infants in two hospitals were colonized by nosocomially acquired bacteria despite a human milk diet, and the resulting gut microbiomes, absent intervention with B. infantis EVC001, developed comparably to reports in the literature on the preterm infant gut microbiome [1,2,10].…”
Section: Discussionmentioning
confidence: 99%